Pelatihan Rekonsiliasi Fiskal Serta Pengisian SPT Tahunan PPH Badan - Linawati L; Arifin A; Hidayatul Muarifin; Saenah S (Yayasan Daarul Huda Kruengmane, 2023)
Community service activities aim to provide training to understand fiscal reconciliation and filling out the Annual Corporate Income Tax Return. Community service is carried out at PT Vertikal Trimitra Selaras which is located in the South Jakarta area. Participants who attended this activity as many as 6 (six) people. The methods applied are the lecture method, tutorial practice, and discussion. The method used in this activity is giving lectures in the form of material related to corporate income tax, demonstrations and practice of preparing fiscal reconciliations and the last method is discussion related to the material presented and other tax issues. The result of this community service activity is that the enthusiasm of the participants is quite large as can be seen from the activeness of the participants to ask questions and the resource persons are quite responsive and communicative in providing solutions, thus adding insight to management, especially the accounting and tax departments as the par that manages company finances.